Letter from James Harmon to John Devoy thanking him on behalf of several clubs - Harmon, James; Devoy, John, 1842-1928 (1889)
Letter of thanks from Harmon to Devoy on behalf of several clubs that Devoy has agreed to speak at. Harmon adds he will communicate further when the committee meets.
Letter on headed paper " Office of / Snyder & McCran, / Dealers in / Hides. Fat, Calfskins Etc/ 667 & 669 Henderson Street / Jersey City".
Keywords: Devoy, John, -- 1842-1928 -- Correspondence; Irish Americans -- Political activity -- 19th century; Irish Americans -- History -- 19th century; Irish Americans -- Societies, etc; Ireland -- History -- 1837-1901; Ireland -- Politics and government -- 1837-1901; Ireland -- Foreign relations -- United States; United States -- Foreign relations -- Ireland